De facto fiscal space and fiscal stimulus: Definition and assessment - Joshua Aizenman; Yothin Jinjarak (University of California, Economics Department, 2010)
We define the notion of 'de facto fiscal space' of a country as the inverse of the outstanding public debt relative to the de facto tax base, where the latter measures the realized tax collection, averaged across several years to smooth for business cycle fluctuations. We apply this concept to account for the cross-country variation in the fiscal stimulus associated with the global crisis of 2009-2010. We find that greater de facto fiscal space prior to the global crisis, higher GDP/capita, and higher financial exposure to the US, were associated with a higher fiscal stimulus/GDP during 2009-2010. Intriguingly, higher trade openness has been associated with lower fiscal stimulus.
Keywords: E62; F42; O23; 330; fiscal space; fiscal stimulus; trade openness; Öffentliche Schulden; Steueraufkommen; Konjunkturpolitik; Finanzpolitik; Konjunktur; Multiplikator; Finanzmarktkrise; Welt